The macrophage stimulating anti-cancer agent, RRx-001, protects against ischemia-reperfusion injury. Issue 6 (3rd June 2017) - Cabrales, Pedro; Caroen, Scott; Oronsky, Arnold; Carter, Corey; Trepel, Jane; Summers, Thomas; Reid, Tony; Oronsky, Neil; Lybeck, Michelle; Oronsky, Bryan
ABSTRACT: Background : RRx-001, a clinical macrophage-stimulating anti-cancer agent that also produces nitric oxide (NO) was studied in a model of ischemia-reperfusion injury. Methods : The production of NO is dependent on the oxygen tension because nitric oxide synthases convert l-arginine to NO and l-citrulline in the presence of O2 . Since the P450 enzymes, which metabolize nitrate esters such as nitroglycerin are dependent on oxygen, the generation of 'exogenous' NO is also sensitive to alterations in tissue PO2 . I/R injury was studied in a hamster chamber window, with compression of the periphery of the window for 1 h to induce ischemia. Animals received RRx-001 (5 mg/kg) 24 h before ischemia and sodium nitrite (10 nmols/kg) was supplemented 10 min after the start of reperfusion. Vessel diameter, blood flow, adherent leukocytes, and functional capillary density were assessed by intravital microscopy at 0.5, 2, and 24 h following the release of the ischemia. Results : The results demonstrated that, compared to control, RRx-001 preconditioning increased blood flow and functional capillary density, and preserved tissue viability in the absence of side effects over a sustained time period. Conclusion : Thus, RRx-001 may serve as a long-lived protective agent during postsurgical restoration of flow and other ischemia-reperfusion associated conditions, increasing blood flow and functional capillary density as well as preserving tissue viability in the absence of side effects.